2019
DOI: 10.1111/jmp.12411
|View full text |Cite
|
Sign up to set email alerts
|

An assay of drug‐induced emesis in the squirrel monkey (Saimiri sciureus)

Abstract: Background Emesis has significant evolutionary value as a defense mechanism against ingested toxins; however, it is also one of the most common adverse symptoms associated with both disease and medical treatments of disease. The development of improved antiemetic pharmacotherapies has been impeded by a shortage of animal models. Methods The present studies characterized the responses of the squirrel monkey to pharmacologically diverse emetic drugs. Subjects were administered nicotine (0.032‐0.56 mg/kg), lithiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 75 publications
(137 reference statements)
0
5
0
Order By: Relevance
“…Notably, D 9 -THC and mAEA were more effective at blocking nicotine-induced than LiCl-induced emesis. Both emetics have been shown to reliably produce emesis in several species, including the squirrel monkey, but may act via different mechanisms (Lee et al, 1978;Beleslin and Krstic, 1987;Billig et al, 2001;Parker et al, 2004Parker et al, , 2009Wooldridge and Kangas, 2019). Nicotine primarily acts at nicotinic receptors in the area postrema, or the "chemoreceptor trigger zone," of the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Notably, D 9 -THC and mAEA were more effective at blocking nicotine-induced than LiCl-induced emesis. Both emetics have been shown to reliably produce emesis in several species, including the squirrel monkey, but may act via different mechanisms (Lee et al, 1978;Beleslin and Krstic, 1987;Billig et al, 2001;Parker et al, 2004Parker et al, , 2009Wooldridge and Kangas, 2019). Nicotine primarily acts at nicotinic receptors in the area postrema, or the "chemoreceptor trigger zone," of the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Both D 9 -THC and, to a lesser extent, mAEA also reduced the hypersalivation that accompanied nicotine-or LiCl-induced emesis, and consistent with the involvement of CB 1 receptor mechanisms, these cannabinergic effects could be blocked by rimonabant. Hypersalivation is thought to be a prodromal sign that often accompanies and worsens the subjective experience of emesis (Sanger and Andrews, 2006;Kenward et al, 2015;Wooldridge and Kangas, 2019). The ability of cannabinoid agonists to abate hypersalivation may therefore be a means of alleviating such distress and, consequently, reflects a desirable feature of their medicinal value.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Enteric nervous system and vagal nerves along with the myenteric and minor plexi regulate the peristalsis movement of the gut mucosa [72]. Abnormal contraction directly promotes the etiology of emesis via M receptor, D receptor, and GABA receptor [73]. In the number of preclinical and clinical studies, it was found that THC and CBD exert antiemetic action via inhibition of various neurotransmitter from the aforementioned receptors [74].…”
Section: Emesis and Cannabismentioning
confidence: 99%